Screening for the causes of refractory hypoxemia in critically ill patients: A case report - Liu, Wanglin; Ding, Xin; He, Huaiwu; Long, Yun; Cui, Na (Frontiers in Medicine, 2022)
Hypoxemia is defined as a low oxygen level in the blood. It is most commonly seen in critically ill patients and is a very common reason for admitting to intensive care unit (ICU). Hypoxemia could cause tissue hypoxia and lead to organ failure and life-threatening conditions [1]. There are various causes of hypoxemia including hypoventilation, lung ventilation/perfusion mismatch, right-to-left shunt, diffusion impairment, and low inspired partial pressure of oxygen [2]. Identifying the right cause and correcting hypoxemia in time is crucially important for critical patients. The authors present a case of middle-aged patient who developed unusual acute and severe hypoxemia after receiving a congenital atrial defect repair surgery. A series of assessments were performed for this patient to identify and treat the severe hypoxemia.